The Propaganda Power of Protest Songs: the Case of Madison's Solidarity Sing-Along - Sheryl Tuttle Ross (Contemporary Aesthetics, 2013)
The aim of this paper is to examine the propaganda power of Madison’s Solidarity Sing-Along. To do so, I will modify the Epistemic Merit Model of propaganda so that it can account for a broader spectrum of propaganda. I will show how this is consistent with other accounts of musical pragmatics and the potential political function of songs and music. This will provide the ground for a robust interpretation of the political meanings of the Solidarity Sing-Along. I will assume the Madison protests and the Solidarity Sing-Along can be considered a paradigm case of peaceful protest as it has been claimed that the Madison protest and the role of art within those protests set the stage for the Occupy Movement protests later in the same year.